Respuesta :
Answer:
x=4
Step-by-step explanation:
3(x+2) = 2(x+5)
Distribute
3x+6 = 2x+10
Subtract 2x from each side
3x-2x+6 = 2x-2x+10
x +6 = 10
Subtract 6 from each side
x+6-6 = 10-6
x = 4
Answer:
x = 4
Step-by-step explanation:
Original Equation:
3(x + 2) = 2(x + 5)
Use distributive property
3 · x = 3x
3 · 2 = 6
Your equation should look like this now:
3x + 6 = 2(x + 5)
Use distributive property for the other side
2 · x = 2x
2 · 5 = 10
Your equation:
3x + 6 = 2x + 10
Subtract 6 from both sides
3x = 2x + 4
Subtract 2x from both sides
1x = 4
Divide both sides by 1
x = 4
Hope this helped :)
Please consider Brainliest :)